Mitigating Wildlife Spillover in the Clinical Setting: How Physicians and Veterinarians Can Help Prevent Future Disease Outbreaks - Tam Tran, MD, PhD, MA; Sherrie Xie, VMD, PhD (Elsevier, 2024)
Introduction: The transmission of pathogens from wildlife to humans is a major global health threat that has been highlighted by the proposed origins of the COVID-19 pandemic. Numerous barriers impede pathogen spillover events from ensuing widespread human transmission, but human activity has accelerated the frequency of spillovers and subsequent disease outbreaks, in part through a booming wildlife trade whose impacts on health are not well understood. Methods: A literature review was conducted to examine the risk that the wildlife trade poses to public health and the degree to which these risks are recognized and addressed in clinical practice and medical and veterinary education. Results: The illicit aspects of the wildlife trade challenge efforts to understand its impacts on health. The U.S. and Europe play a leading role in the global wildlife trade that often goes unacknowledged. In particular, the consumption of wild meat and ownership of exotic pets poses public health risks. The potential role of clinicians is underutilized, both in the clinical setting and in clinical education. Discussion: Physicians and veterinarians have the unique opportunity to utilize their clinical roles to address these knowledge gaps and mitigate future outbreaks. We outline a multifaceted approach that includes increasing clinical knowledge about the ecology of zoonotic diseases, leveraging opportunities for mitigation during patient/client-clinician interactions, and incorporating One Health core competencies into medical and veterinary school curricula.